The relationships between role strain, mental toughness and mental health amongst adolescent athletes - Morrison, J.; Coulter, T. J.; Polman, R. (Advanced Exercise and Health Science, 2024)
Objective Adolescent athletes are required to manage numerous roles to succeed. This study examined the association of role strain and mental health symptomology and the potential mediating role of mental toughness. In addition, the role of gender and sport type was examined. Method: 128 Adolescent athletes (males = 40; females = 88; mean age = 18.34 years; SD = 2.20) from diverse sports in Australia completed an online survey (Qualtrics) which included demographic information, the Role Strain Questionnaire for Junior Athletes (RSQ-JA), Depression, Anxiety and Stress Scale (DASS-21) and Very Short Mental Toughness Questionnaire (VS-MTQ). Results: Regression analysis showed that role strain (ambiguity) explained 31% of the variance in depression, 27.2% in anxiety (ambiguity, underload) and 30.5% of stress (overload, ambiguity). Mediation analysis showed that mental toughness did not mediate the association between role strain and mental health symptomology. However, higher levels of mental toughness was associated with decreased depression, anxiety and stress symptomology. There were no associations for gender and sport type with role strain or mental health except for stress, with females reporting higher levels (mean 19.67, SD = 9.05 for females and 15.21, SD = 8.36 for males, p = 0.01) with a small effect size. Conclusion: Role strain and mental toughness both influence mental health symptomology. This allows for the development of interventions which can reduce role strain or enhance mental toughness in adolescent athletes to improve their mental wellbeing.